2014
DOI: 10.1155/2014/423120
|View full text |Cite
|
Sign up to set email alerts
|

Response to Statin Therapy in Obstructive Sleep Apnea Syndrome: A Multicenter Randomized Controlled Trial

Abstract: Rationale. Accumulated evidence implicates sympathetic activation as inducing oxidative stress and systemic inflammation, which in turn lead to hypertension, endothelial dysfunction, and atherosclerosis in obstructive sleep apnea (OSA). Statins through their pleiotropic properties may modify inflammation, lipid profile, and cardiovascular outcomes in OSA. Methods. This multicenter, randomized, double-blind study compared the effects of atorvastatin 40 mg/day versus placebo over 12 weeks on endothelial function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…The impact of statin administration on arterial stiffness has been examined in healthy individuals and in subjects with either hypertension, hypercholesterolaemia, chronic obstructive pulmonary disease, obstructive sleep apnoea, chronic kidney disease or obesity. [17][18][19][20][21][22][23][24][25][26][27] The results of these studies were either negative [25][26][27] or they showed a non-significant trend for reduction of PWV. 17,18,21 The study with the longest duration was performed by Fassett et al 18 in 37 patients with chronic kidney disease who were randomly assigned to receive either 10 mg of atorvastatin or placebo for 3 years.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The impact of statin administration on arterial stiffness has been examined in healthy individuals and in subjects with either hypertension, hypercholesterolaemia, chronic obstructive pulmonary disease, obstructive sleep apnoea, chronic kidney disease or obesity. [17][18][19][20][21][22][23][24][25][26][27] The results of these studies were either negative [25][26][27] or they showed a non-significant trend for reduction of PWV. 17,18,21 The study with the longest duration was performed by Fassett et al 18 in 37 patients with chronic kidney disease who were randomly assigned to receive either 10 mg of atorvastatin or placebo for 3 years.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, several studies in non-diabetic population reported conflicted results. [17][18][19][20][21][22][23][24][25][26][27] Two recent meta-analyses, examined the impact of statin treatment on PWV and concluded that statin treatment reduced PWV; however, these meta-analyses did not include studies in people with T2DM, and there was significant heterogeneity in the studies analysed. 28,29 The main aim of this prospective non-randomized observational study was to examine the impact of treatment with either 10 mg atorvastatin plus diet or diet alone for 12 months on cf-PWV in subjects with T2DM and dyslipidaemia, who were free of clinically apparent macrovascular disease.…”
Section: Effect Of 12-month Intervention With Low-dose Atorvastatin Omentioning
confidence: 99%
“…The correlation between change in inflammatory parameters and the effect of CPAP on lipid profiles could not be concluded because only a few of recruited studies provided such information. However, one recent study by Joyeux-Faure showed that the statin therapy known for anti-inflammatory effect had no effect on inflammatory or autonomic activity markers despite its lipid-lowering effect [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among patients undergoing percutaneous coronary intervention, OSA was an independent predictor of lower effectiveness of antiplatelet therapy ( 120 ). Statin treatment in OSA patients lowered blood pressure and corrected lipid panel, but did not affect early atherosclerosis ( 121 ). This observation leads to questioning whether platelets should be considered a therapeutic target in OSA or rather a component of pathogenetic pathways.…”
Section: Platelets As Immune Cells Mediating Cvdmentioning
confidence: 99%